2021
DOI: 10.1096/fj.202101134r
|View full text |Cite
|
Sign up to set email alerts
|

CD226 deficiency promotes glutaminolysis and alleviates mitochondria damage in vascular endothelial cells under hemorrhagic shock

Abstract: Hemorrhagic shock (HS) is common in clinical emergencies, leading to millions of deaths each year globally. CD226 is a costimulatory adhesion molecule expressed on both immune cells and endothelial cells (ECs) to regulate their metabolic activity and function. As endothelial dysfunction occurs after HS, the roles CD226 plays in vascular EC metabolism were investigated. CD226 fl/fl Tek cre mice were adopted to achieve vascular EC-specific knockout of CD226, and subjected to HS modelling. Serum levels of crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Glutamine catabolism may provide the additional energy required by HSCs during chronic hypoxia ( 28 ). We found that GLS1 levels increased in both patients and in an animal model for NASH, and that this was dependent on fibrosis, suggesting that GLS1 may enhance glutaminolysis associated with hypoxia-induced HIF-2α ( 37 , 65 ). Further research using LX-2 cells in vitro could be helpful to understand the relationship between HIF-2α and glutaminolysis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Glutamine catabolism may provide the additional energy required by HSCs during chronic hypoxia ( 28 ). We found that GLS1 levels increased in both patients and in an animal model for NASH, and that this was dependent on fibrosis, suggesting that GLS1 may enhance glutaminolysis associated with hypoxia-induced HIF-2α ( 37 , 65 ). Further research using LX-2 cells in vitro could be helpful to understand the relationship between HIF-2α and glutaminolysis.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have revealed that both HIF-1α and HIF-2α ( 11 , 37 ) control the metabolism of reprogrammed hepatocytes ( 38 , 39 ). HIF-1α and HIF-2α recognise and bind hypoxia response elements to activate the cellular response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…It was not established if CD226 signaling modulates metabolism in NK cells. Recently, CD226 signaling was reported to promote glycolysis in endothelial cells [ 48 ]. Similarly, we noted diminished glycolysis in NK cells from LTBI+ people after CD226 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Using the UCSC genome browser [41] integrating information about interactions between GeneHancer regulatory elements and genes expression (see S4 Fig) , we identified CD226 as a strong biological candidate. CD226 codes for a glycoprotein expressed at the surface of several types of cells, including blood cell, and several studies have shown that it was associated with vascular endothelial dysfunction [42][43][44]. Genetic variants in CD226 have also been found associated with several blood cell traits including platelets, white blood cells (e.g.…”
Section: Plos Geneticsmentioning
confidence: 99%